2022
DOI: 10.1186/s12948-022-00167-y
|View full text |Cite
|
Sign up to set email alerts
|

The risk of anaphylaxis behind authorized COVID-19 vaccines: a meta-analysis

Abstract: Background A serious allergic reaction that may occur in response to medical products is anaphylaxis, which potentially can lead to anaphylactic shock. In the light of recent COVID-19 pandemic, much public attention had been paid to the severe allergic reactions occurring after COVID-19 vaccination. Therefore, in our study we would like to investigate the risk of authorized COVID-19 vaccines to induce anaphylactic reaction, anaphylactoid reaction, anaphylactic shock and anaphylactoid shock. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 38 publications
2
20
0
2
Order By: Relevance
“…Regarding sex, we found a higher proportion of female participants, who showed more pain or swelling at the injection site, muscle pain, and swollen glands ( p < 0.05) compared to the male group and other groups. These results are similar to those seen in several studies [ 24 , 25 , 26 ]. Despite the differences in the distribution of the participants according to age, in the group younger than 50 years (81.2%) and the group older than 50 years (18.8%), the presentation of self-reported ESAVIs showed significant results ( p < 0.05) that participants younger than 50 years had more ESAVIs, especially mild and moderate symptoms, in comparison with those older than 50 years.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding sex, we found a higher proportion of female participants, who showed more pain or swelling at the injection site, muscle pain, and swollen glands ( p < 0.05) compared to the male group and other groups. These results are similar to those seen in several studies [ 24 , 25 , 26 ]. Despite the differences in the distribution of the participants according to age, in the group younger than 50 years (81.2%) and the group older than 50 years (18.8%), the presentation of self-reported ESAVIs showed significant results ( p < 0.05) that participants younger than 50 years had more ESAVIs, especially mild and moderate symptoms, in comparison with those older than 50 years.…”
Section: Discussionsupporting
confidence: 93%
“…[18] , [19] , [20] Anaphylaxis has been reported following receipt of mRNA, ChAdOx1 and Ad26.COV2.S vaccines. [21] , [22] Rare cases of acute myocardial infarction have been reported following vaccination with BNT162b2. [23] , [24] , [25] …”
Section: Introductionmentioning
confidence: 99%
“…While viral infections may activate MC through binding of viral antigens to RIG-1 or TLR and C5a to C5aR/CD88, COVID-19 infection has previously not been related to significant MC activation symptoms in mastocytosis patients [ 33 ]—a finding which has been replicated in this study. Because, in mRNA vaccines, mRNA is enclosed in a PEGylated nanolipid envelope, a potential IgE-mediated cause for anaphylaxis has been extensively studied, but conflicting findings have arisen [ 10 , 11 , 13 , 34 , 35 , 36 , 37 ]. Moreover, complement-mediated MC activation (so-called complement activation-related pseudoallergy, CARPA) induced by IgM/IgG immunocomplexes against PEG/polysorbate has also been suggested [ 8 , 13 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several studies have shown these vaccines to be safe, with an incidence of anaphylaxis ranging from 7.91 [ 9 ] to 10.67 [ 10 ] cases per million doses; which is lower than that reported for rabies, tick-borne encephalitis, measles-mumps-rubella-varicella, and human papillomavirus vaccines [ 10 ]. mRNA vaccines seem to be overall safer regarding anaphylaxis than their viral vector counterparts [ 11 ].…”
Section: Introductionmentioning
confidence: 99%